2016
DOI: 10.1073/pnas.1515613113
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma virus M156 is a specific inhibitor of rabbit PKR but contains a loss-of-function mutation in Australian virus isolates

Abstract: Myxoma virus (MYXV) is a rabbit-specific poxvirus, which is highly virulent in European rabbits. The attenuation of MYXV and the increased resistance of rabbits following the release of MYXV in Australia is one of the best-documented examples of host-pathogen coevolution. To elucidate the molecular mechanisms that contribute to the restriction of MYXV infection to rabbits and MYXV attenuation in the field, we have studied the interaction of the MYXV protein M156 with the host antiviral protein kinase R (PKR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 29 publications
5
77
0
Order By: Relevance
“…However, the transcription start sites of most MYXV mRNAs have not been mapped and hence actual expression may differ from that assigned [39, 31, 40]. In the UK sequences, mutations upstream of the M000 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the transcription start sites of most MYXV mRNAs have not been mapped and hence actual expression may differ from that assigned [39, 31, 40]. In the UK sequences, mutations upstream of the M000 .…”
Section: Resultsmentioning
confidence: 99%
“…The latter two proteins are important virulence factors (39,40). In addition, along with other viruses, BD44 possesses a mutation L71P in M156 (an inhibitor of the antiviral protein kinase R), which has been demonstrated to cause loss of function (41). Thus, the loss of major virulence functions is compatible with high virulence, suggesting compensatory mutations are playing an important role.…”
Section: Discussionmentioning
confidence: 99%
“…(knockdown resistant) (human), pSG5-mmPKR (mouse), and pSG5-oaPKR (sheep) were previously described. 9,19 Bos taurus (cow) PKR was cloned from MDBK cells and the sequence was identical to NP_835210.2. Capra hircus (goat) PKR (XM_005686488.2) was synthesized (GENEWIZ) and subcloned from the pUC57 vector into pSG5 to generate pSG5-chPKR.…”
Section: Plasmidsmentioning
confidence: 99%
“…Similarly, we showed that inactivation of M156 inhibited virus replication in rabbit cells. 19 However, very little is known about these PKR-inhibitor interactions in other types of poxviruses.…”
Section: Introductionmentioning
confidence: 99%